Análise da atividade do trabalho de agendamento de consultas de um centro médico. - Fontolan, Daniel (2003)
The Brazilian public health system is constantly criticized by its inefficiency and lack of quality on its services. The Information Systems are powerful tools which can be used to improve the quality and increase the productiveness of these precious jobs, mainly to the needed people. The systems operators job activity is the main component of stored data, which will be analyzed by the decision makers. This dissertation shows how the Activity Analyses can be used to understand the working situations presented in a specialized health treatment unit, hoping to on the proposal of a managing information system that considers the vary and regulation of the employees job.